Kaip įsitikinimai, požiūris ir gebėjimas pasinaudoti galimybėmis daro įtaką startuolių verslo kūrybiškumui - Palos-Sanchez, Pedro (2020)
. This article examines the main factors that affect creativity in startups and how these factors influence entrepreneurial initiative strategies. Fifty individuals from the Extremadura region, Spain, participated in an online questionnaire in 2018 and 2019. SmartPLS was used to create a model of the interactions between variables. The results obtained have important theoretical and practical implications as they add new findings to the current literature on the role played by different factors in the creativity processes used by startups. The model has a strong predictive power (R2 = 42.7%). This work describes internal factors such as the improvement in intellectual and at-titudinal skills for identifying business opportunities as a preliminary step to taking creative business decisions, as well as shaping the future by coordinating potential efforts and actions.